2017
DOI: 10.3390/w9030171
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Groundwater Level on Nitrate Nitrogen Accumulation in the Vadose Zone Beneath a Cotton Field

Abstract: Abstract:In this study, the impacts of groundwater level on nitrate nitrogen accumulation in the vadose zone of a cotton field were investigated. Experiments were conducted in a cotton field at the CAS Ecological Agricultural Experiment Station in Nanpi from 2008 to 2010. A vertical observation well was drilled, and time-domain reflectometry probes and soil solution extractors were installed every 50 cm in the walls of the well to a depth of 5 m. The soil water content was monitored, and soil solution samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…According to the zoning maps of groundwater by Mohammadi et al (2017), nitrate concentration in the dry season in the water resources of Bandar-e Gaz City, Iran, was greater than rainy seasonal [31]. This finding also supports the theory that more precipitation in semiarid climates facilitates land change and results in greater nitrate leaching [32,33]. The estimated HQ using the LPM scenario in the semi-arid climate was 0.17 for infants, 0.64 for children, and 0.25 for adults.…”
Section: Risk Characterizationsupporting
confidence: 68%
“…According to the zoning maps of groundwater by Mohammadi et al (2017), nitrate concentration in the dry season in the water resources of Bandar-e Gaz City, Iran, was greater than rainy seasonal [31]. This finding also supports the theory that more precipitation in semiarid climates facilitates land change and results in greater nitrate leaching [32,33]. The estimated HQ using the LPM scenario in the semi-arid climate was 0.17 for infants, 0.64 for children, and 0.25 for adults.…”
Section: Risk Characterizationsupporting
confidence: 68%
“…Transportation or movement of NO 3 – out of the reaches of the plant rooting zone is termed as leaching, which is affected by various factors, such as soil structure, soil texture, intensity and frequency of precipitation, and irrigation practices ( Sebilo et al, 2013 ; Bijay-Singh and Craswell, 2021 ). In the upland rice systems, N leaching was denoted as inconsequent loss pathways because of higher evaporation than annual precipitation ( Jiao et al, 2017 ; Jankowski et al, 2018 ; Sigler et al, 2020 ). Later, it has been found that frequent precipitation periods during summer could cause drainage of water leading to downward movement of NO 3 – , which is supported by soil textural factors ( Huang T. et al, 2017 ; Manik et al, 2019 ; Hess et al, 2020 ; Kaur et al, 2020 ).…”
Section: Toward Eco-efficient N Managementmentioning
confidence: 99%
“…The soil texture is loam, and the average water holding capacity is 34.2% (m 3 m −3 ). The physical soil properties and soil moisture parameters of different soil horizons at the experimental site are as described by Xiyun Jiao (2017) [31]. The saturated hydraulic conductivity of the top soil layer (0-20 cm) is around 28-30 mm/h.…”
Section: Experimental Site and Farming Systemmentioning
confidence: 99%